MOW strengthening and contourite development over two analog climate cycles (MIS 12-11 and MIS 2-1) in the Gulf of Cadíz: an impact on North Atlantic climate during deglaciation V and MIS 11? - Moal-Darrigade, Paul; Ducassou, Emmanuelle; Giraudeau, Jacques; Bahr, André; Kaboth-Bahr, Stefanie; Hanquiez, Vincent; Perello, Marie-Claire (Global and planetary change, 2022)
High-resolution records from International Ocean Discovery Program (IODP) sites U1386 and U1387 drilled during IODP Expedition 339 into the Faro drift, made it possible to assess the impact of intensifications of the upper core (MOWu) of the Mediterranean Outflow Water (MOW) and of changes in sediment supply on the sedimentation in the northern Gulf of Cadiz since the Middle Pleistocene. This work focuses on the comparison of records covering Marine Isotope Stage (MIS) 2-1 and MIS 12-11, in order to investigate the behaviour and circulation regime of the MOWu over two climatic cycles of similar astronomical configurations and their associated deglaciation. The analysis of facies established on the basis of grain size, XRF core-scanning, and carbonate content revealed contourite beds formed by the MOWu during MIS 11 and MIS 1 and deglaciations (deglaciation V and I). Contourite sequences show that MOWu velocity at the seabed was higher during MIS 2-1 than during MIS 12-11, and that sediment supply was different between these two climatic cycles. While overall low during MIS 12-11, MOWu intensity increased during deglaciation V and MIS 11 and preceded large ice rafted events and cooling in the North Atlantic Ocean. As a major element of the MOW, MOWu strengthening during deglaciation V likely contributed to higher heat and moisture transport towards the high latitudes inducing a slight increase of calving and size of boreal ice sheets. The MOW-derived injection of heat and salt in the North Atlantic Ocean during deglaciation V might have contributed, through reactivation of the upper AMOC, to the switch of the Atlantic thermohaline circulation from a glacial to an interglacial mode.
Available online 11 December 2021
Gesehen am 10.02.2022